Toni Morrison : writing the moral imagination - Smith, Valerie, 1956- (Chichester, West Sussex, UK ; Malden, MA : Wiley-Blackwell, 2012)
"In this compelling new study, Valerie Smith analyzes the celebrated fiction of Morrison in relation to her critical writing about the process of reading and writing literature, the relationship between readers and writers, and the cultural contributions of African-American literature"--
The Bluest Eye and Sula -- Song of Solomon and Tar Baby -- Beloved -- Jazz and Paradise -- Books for young readers, Love and A Mercy -- Home.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher.
Keywords: Morrison, Toni -- Criticism and interpretation; Morrison, Toni; Morrison, Toni; LITERARY CRITICISM / American / General; Electronic books; Criticism, interpretation, etc